Comparative study of single and multi domain CVD graphene using large‐area Raman mapping and electrical transport characterization. Issue 11 (27th September 2016) - Thodkar, Kishan; El Abbassi, Maria; Lüönd, Felix; Overney, Frédéric; Schönenberger, Christian; Jeanneret, Blaise; Calame, Michel
Abstract : We systematically investigate the impact of granularity in CVD graphene films by performing Raman mapping and electrical characterization of single (SD) and multi domain (MD) graphene. In order to elucidate the quality of the graphene film, we study its regional variations using large‐area Raman mapping and compare the G and 2D peak positions of as‐transferred chemical vapor deposited (CVD) graphene on SiO2 substrate. We find a similar upshift in wavenumber in both SD and MD graphene in comparison to freshly exfoliated graphene. In our case, doping could play the dominant role behind the observation of such upshifts rather than the influence due to strain. Interestingly, the impact of the polymer‐assisted wet transfer process is the same in both the CVD graphene types. The electrical characterization shows that SD graphene exhibits a substantially higher (a factor 5) field‐effect mobility when compared to MD graphene. We attribute the low sheet resistance and mobility enhancement to a decrease in charge carrier scattering thanks to a reduction of the number of grain boundaries and defects in SD graphene. Abstract : Single and multi domain chemical vapor deposited (CVD) graphene films are systematically investigated using large area Raman and electrical characterization. It is found that the polymer‐assisted wet transfer process has a similar influence of p‐doping in both types of CVD graphene films. Moreover, electrical characterization of single domain graphene shows higher (a factor 5) field effect mobility when compared to a multi domain graphene.